1967
DOI: 10.1042/bj1040404
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of a hyaluronic acid preparation in a density gradient. The isolation and identification of a chondroitin sulphate

Abstract: 1. Following the suggestion of Nichol, Ogston & Preston (1967) that hyaluronic acid, prepared by filtration from ox synovial fluid, contains a component of high density, such material has been detected and isolated by equilibrium sedimentation in a density gradient of caesium chloride. 2. This material (fraction III) has been characterized as a chondroitin sulphate-protein complex of average molecular weight about 250000. Its amino acid pattern is characteristic of such complexes present in cartilage. It conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

1969
1969
1987
1987

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…Franek and Dunstone (1966), Silpananta et al (1967) and Creeth and Denborough (1970) consider that protein and polysaccharide sedimenting together in caesium chloride gradients are covalently linked glycoproteins, and they have applied this method to separate protein and glycoprotein quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…Franek and Dunstone (1966), Silpananta et al (1967) and Creeth and Denborough (1970) consider that protein and polysaccharide sedimenting together in caesium chloride gradients are covalently linked glycoproteins, and they have applied this method to separate protein and glycoprotein quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier biochemical work revealed the presence of chondroitin sulfate in synovial fluid (19)(20)(21) and showed that there were increases in the CS content relative to that of hyaluronic acid (2Q,21). Others have described cartilage proteoglycan-like fragments in normal ox synovial fluid of molecular weight 250,000 (22). Recently, using a polyclonal antibody to cartilage proteoglycan, increased amounts of proteoglycan were detected by enzyme-linked immunosorbent assay in the synovial fluids of patients with reactive arthritis (23).…”
mentioning
confidence: 99%
“…AnaIytical density gradient sedimentation was performed in a Beckman model E analytical ultracentrifuge [5,6] Serological activity was determined by the capacity of the substances to inhibit in specific haemagglutination tests [17]. Fig.…”
Section: Sedimentationmentioning
confidence: 99%